Factores Sociales que Intervinieron en el Levantamiento Indígena Liderado por Fernando Daquilema en 1871. - Dávalos Vacacela, Henry Cley (2025)
The present research work titled "The Social Factors Involved in the Indigenous Uprising Led by Fernando Daquilema in 1871" was a fundamental episode of resistance in Ecuador's republican history. This research explores how the structures of domination during García Moreno's government created conditions for this uprising in the Chimborazo Province. The general objective was to determine "The social factors of the second half of the 19th century that intervened in the indigenous uprising in Ecuador led by Fernando Daquilema in 1871." This research project employed a Case Study methodology with a qualitative approach and descriptive-explanatory scope, using documentary analysis from primary and secondary sources to achieve a rigorous analysis of the phenomenon. The findings revealed four coinciding social factors: the repressive economic and social structure of the hacienda and concertaje system; the political organization of the Garcian State, which aggravated forced labor by demanding subsidiary work and the obligation of tributes such as the tithe; the cultural dimension manifested a strong tension between the traditional systems and forms of indigenous peoples and the standardized model promoted by the State; and the ethnic-racial component that justified marginalization and geographical isolation and the social acceptance of violence. It was concluded that Daquilema's uprising was not a spontaneous response to specific abuses but rather the manifestation of deep structural contradictions in 19th-century Ecuadorian society. These social factors created conditions that made organized resistance inevitable, while the demands raised set precedents that continue to fuel the struggles for indigenous peoples' rights in contemporary Ecuador.